Mammalian Target of Rapamycin Inhibitors Induce Tumor Cell Apoptosis In Vivo Primarily by Inhibiting VEGF Expression and Angiogenesis - Frost, Patrick (Hindawi Publishing Corporation, 2013)
We found that rapalog mTOR inhibitors induce G1 arrest in the PTEN-null HS Sultan B-cell lymphoma line in vitro, but that administration of rapalogs in a HS Sultan xenograft model resulted in significant apoptosis, and that this correlated with induction of hypoxia and inhibition of neoangiogenesis and VEGF expression. Mechanistically, rapalogs prevent cap-dependent translation, but studies have shown that cap-independent, internal ribosome entry site (IRES)-mediated translation of genes, such as c-myc and cyclin D, can provide a fail-safe mechanism that regulates tumor survival. Therefore, we tested if IRES-dependent expression of VEGF could likewise regulate sensitivity of tumor cells in vivo. To achieve this, we developed isogenic HS Sultan cell lines that ectopically express the VEGF ORF fused to the p27 IRES, an IRES sequence that is insensitive to AKT-mediated inhibition of IRES activity and effective in PTEN-null tumors. Mice challenged with p27-VEGF transfected tumor cells were more resistant to the antiangiogenic and apoptotic effects of the rapalog, temsirolimus, and active site mTOR inhibitor, pp242. Our results confirm the critical role of VEGF expression in tumors during treatment with mTOR inhibitors and underscore the importance of IRES activity as a resistance mechanism to such targeted therapy.